Career outcomes and diversity: New scholarship and directions - Andresen, M.; Bosak, J.; Douglas T. Hall; Heijden, B.; Duarte, H.; Goštautaitė, B.; Kim, N.; Lam, J.; Verbruggen, M.; Afiouni, F.; Apospori, E.; Bagdadli, S.; et al. (Academy of Management Proceedings, 2024)
Academic publications on careers date back to the early 20th century. One of the earliest publications, for example, is Parson's trait and factor theory, which was developed in the early 1900s but not published until after his death in 1909. The continued interest in career studies since then is not surprising, as the "evolving sequence of a person's work experiences over time" (Arthur et al., 1989, p. 4) has also developed along with spatial, ontic and temporal changes in the context of organizations (Gunz & Mayrhofer, 2017). However, taking a critical look at the publications in career research, a majority of the studies refer to the careers of middle-class, middle-aged, Caucasian, Catholic, male career actors, preferably MBA graduates. Indeed, this focus is WEIRD (Heinrich et al., 2010) – it reflects the generalization of the Western, Educated, Industrialized, Rich and Democratic population to the rest of the world. This is even though Parsons already in 1909 differentiated between traits and factors in his career theory. The 'factors' refer to possible jobs and occupations, while the 'traits' refer to the qualities of people who aspire to a career. Especially when it comes to ‘traits”, much research is still needed. A growing discourse in the field of diversity assumes that the samples do not fully represent the occupations and traits of today's highly heterogeneous workforce. For example, employability – a term that continues to characterize career research (Fugate et al., 2021) – arguably looks different depending on one's position in social space. In the careers literature measures and analyses of career outcomes typically focus on objective dimensions including income, job level, promotion history, and occupational status; and subjective aspects such as career satisfaction, perceived career success, or commitment (Spurk et al., 2019). However, too little is known about the extent to which the diversity characteristics of career actors influence their career outcomes. Are the seeds for career success already sown in one’s childhood (and is career success therefore a function of psychological or social inheritance)? Do career outcomes depend on one’s decisions (as in the case in path dependency) and are they the result of individual action? What role do structural factors play (e.g., support from superiors, mentoring) and to what extent do they have a positive or negative effect on career outcomes? After all, career outcomes will look different in certain parts of the world (see e.g., Briscoe et al., 2021). Which contextual factors at country level (e.g., educational expenditure) moderate the observed correlations between diversity and career outcomes and have the potential to bring about change? Against this backdrop, the symposium presents papers which address five diversity-related issues connected to social origin, age, gender, parental status, and culture. All papers combine a strong theoretical background and empirical focus and use a range of methodologies, ranging from large-scale surveys to experiments to establish causation. Four papers employ multi-national datasets, with the ‘social origin’ paper (Paper 1) using survey data from an impressive 19,452 individuals in 30 countries, the ‘age’ paper (Paper 2) using survey data from 6,968 individuals in 29 countries, the ‘gender and parental status’ paper (Paper 4) using survey data from 6,727 professionals and managers in 27 countries, and the ‘culture’ paper (Paper 5) using survey data from 6,134 individuals nested in 12 countries. Each of these studies is based on a multi-level analysis and examination of macro-level variables – relational social capital (Paper 1), education expenditure and unemployment rate (Paper 2), gender inequality index (Paper 4), individualism/collectivism (Paper 5) – as cross-level moderators. The further study (Paper 3) uses 396 undergraduate business students from a Canadian University and 329 American employees to experimentally test the effect of allyship (vs no allyship) on career consequences for women and men. These diverse studies are aligned in their effort to provide in-depth insights and a better understanding of careers and career-related outcomes through a diversity perspective – that is, do career outcomes differ for women and minority group members – with the career outcomes under examination in these papers including subjective financial career success (Paper 1), career resilience and career optimism (Paper 2), career consequences in form of perceived promotability, leadership effectiveness, and recommendations for work-related rewards and penalties (Paper 3), proactive career behaviors (Paper 4), and work engagement as a result of perceived career self-congruence (Paper 5).